2018
DOI: 10.1186/s12889-018-6119-9
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence in the East Azerbaijan province of Iran in 2015–2016: results of a population-based cancer registry

Abstract: BackgroundFew countries in the Middle East have a population-based cancer registry, despite a clear need for accurate cancer statistics in this region. We therefore established a registry in the East Azerbaijan province, the sixth largest province in northwestern Iran.MethodsWe actively collected data from 20 counties, 62 cities, and 44 districts for the period between 20th March 2015 and 19th March 2016 (one Iranian solar year). The CanReg5 software was then used to estimate age-standardized incidence rates (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 43 publications
(39 reference statements)
1
21
0
Order By: Relevance
“…Breast cancer is the most frequent cancer in women, and the second most common cancer across the globe [1]. Reports showed that breast cancer was the third most common cancer in the study region of Iran [14]. The highest occurrence has been reported from the United States and Western Europe, while the lowest rates belong to the East Asia [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is the most frequent cancer in women, and the second most common cancer across the globe [1]. Reports showed that breast cancer was the third most common cancer in the study region of Iran [14]. The highest occurrence has been reported from the United States and Western Europe, while the lowest rates belong to the East Asia [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Although it was originally based on pathology data, it has since been developed and improved to the point where we have established a standardized population-based cancer registry of data obtained from different sources. Cancers of the gastrointestinal tract are among the most common and important cancers in Northwestern Iran and East Azerbaijan [6]. Gastric cancer in particular continues to be the most common among men in this region [4, 6].…”
Section: Discussionmentioning
confidence: 99%
“…The population-based cancer registry program was completed in 2015 and we expect the results of this to be published soon. This registry sources data from pathology laboratories, hospital medical records, and cause of death registries, as well as radiotherapy, hematology, and imaging departments, to estimate the rates of different cancers in East Azerbaijan Province [6].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Completeness of coverage was measured as the number of reported cases of cancer per year divided by the number of gastrointestinal tract cancers in Iran estimated by the WHO [17]. This demonstrated a 60-70% coverage of all cancer cases [18]. We identified 161 women who were diagnosed as having colorectal cancer.…”
Section: Populationmentioning
confidence: 99%